Robust two degrees‐of‐freedom single‐current control strategy for LCL‐type grid‐connected DG system under grid‐frequency fluctuation and grid‐impedance variation. Issue 14 (1st November 2016) - Zhou, Leming; Chen, Yandong; Luo, An; Guerrero, Josep M.; Zhou, Xiaoping; Chen, Zhiyong; Wu, Wenhua
Abstract : For LCL‐type grid‐connected distributed generation (DG) system, the grid‐frequency fluctuation and grid‐impedance variation affect the active/reactive power control accuracy and resonance peak suppression, respectively, which would reduce the system robustness. In this study, a robust two degrees‐of‐freedom single‐current control strategy is proposed, which mainly includes the synchronous reference frame quasi‐proportional–integral (SRFQPI) control and robust grid‐current‐feedback active‐damping (RGCFAD) control. The proposed SRFQPI control can compensate the local‐load reactive power, and regulate the instantaneous grid current without steady‐state error regardless of the fundamental frequency fluctuation. Simultaneously, the proposed RGCFAD control effectively damps the LCL‐resonance peak regardless of the grid‐impedance variation, and further improves both transient and steady‐state performances. The stability margin and dynamic response of the overall system are analysed in detail, and the proper parameters are selected without complicated trial. Finally, simulation and experimental results verify the proposed control and design strategies.